Preparation and application of cadmium selenide quantum dots / graphene-sensitized titanium dioxide nanorod photoanode
Patent Information
- Application Number
- CN202510911841.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-02
Smart Images

Figure CN120400919B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the preparation and application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode, belonging to the field of photoelectrocatalysis. Background Technology
[0002] With the continuous development of global society, population growth has driven unprecedented demand for resources, especially energy. Among renewable energy options, solar energy is widely considered the most abundant and environmentally sustainable energy source. Its effective utilization could potentially solve key problems such as resource depletion and environmental pollution. However, the current utilization rate of solar energy is very low; the most important way to utilize solar energy on Earth remains through plant photosynthesis. Therefore, converting solar energy into energy readily available to humankind is the most promising way to solve resource and environmental problems. To utilize solar energy, various methods have been developed, such as photovoltaic power generation and photocatalysis. Recent technological advancements have also spurred the development of various technologies that can directly convert solar energy into electricity, such as solar cell (PC) technology. Although solar energy is the most abundant energy source, and solar cell technology has made significant progress, it still faces many challenges in practical applications. For example, in some solar cells, although the catalytic materials can exhibit high visible light absorption efficiency, with a theoretical power conversion efficiency of up to 44%, the actual light conversion efficiency is not high, making it difficult for the solar cell itself to output high power.
[0003] To address the limitations of single energy conversion technologies, researchers have begun exploring innovative methods that integrate multiple energy conversion pathways, aiming to achieve more efficient and sustainable energy utilization. Among these, designing systems capable of simultaneously converting solar and chemical energy into electrical energy has become a research hotspot. Based on this concept, photocatalytic fuel cells (PFCs) have emerged. These cells cleverly combine the principles of fuel cells (FCs) and solar cells (PCs), achieving dual energy conversion through the synergistic effect of photocatalysis and electrochemical reactions.
[0004] In PFCs, many photocatalytic materials (such as titanium dioxide and carbon nitride) are used to absorb sunlight and generate electron-hole pairs, thereby driving electrochemical reactions. Simultaneously, the fuel cell utilizes the chemical energy of fuels (such as hydrogen, methanol, or glucose) to generate electricity through redox reactions. This dual energy conversion mechanism not only significantly improves the system's power output but also greatly enhances overall energy utilization efficiency. Studies have shown that compared to traditional fuel cells or solar cells, PFCs can achieve higher energy density and longer operating time under the same conditions. However, the development of photocatalytic fuel cells is still in its early stages, and many problems remain to be solved. In a PFC system, the photoanode is undoubtedly one of the most important components, needing to fulfill both the roles of electrocatalyst and photocatalyst to complete the FC and PC activities. Therefore, selecting a suitable photocatalyst has become a key focus of this work. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing and applying a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod (CdSe QDs-PGR / TiO2 NRAs / FTO) photoanode. The prepared cadmium selenide quantum dot / graphene composite material, CdSe QDs-PGR, serves as a TiO2 sensitizer in the photoanode of a photocatalytic fuel cell. It effectively broadens the spectral absorption range of TiO2 to the visible light spectrum and effectively generates light spot separation. The cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod (CdSe QDs-PGR / TiO2 NRAs / FTO) photoanode can effectively generate photocurrent and catalytically oxidize ascorbic acid. The assembled cell can achieve a photocurrent of 187.65 μw / cm². 2 With its high power density, it has promising market application prospects.
[0006] To solve the above-mentioned technical problems, the present invention is implemented using the following technical solution: In a first aspect, the present invention provides a method for preparing a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode (CdSe QDs-PGR / TiO2 NRAs / FTO), comprising the following steps: (1) Preparation of cadmium selenide quantum dot solution; A certain amount of selenium powder was dispersed in anhydrous sodium sulfite solution to prepare Na2SeSO3 solution; mercaptoacetic acid was dispersed in CdCl2 solution and adjusted to alkalinity; at a certain temperature, Na2SeSO3 solution was rapidly injected into CdCl2 solution containing mercaptoacetic acid; after reacting for a period of time, cadmium selenide quantum dot solution was prepared. Preferably, selenium powder is first mixed with anhydrous sodium sulfite, and 20 ml of water is added as a solvent. The mixture is heated to 90°C with continuous stirring. After the reaction is complete, ultrapure water is added to bring the volume to 50 ml to obtain a Na₂SeSO₃ solution. Mercaptoacetic acid is then added to a CdCl₂ solution, and the pH is adjusted to 10 using 0.5 M NaOH. Ultrapure water is then added to bring the volume to 50 ml. The Na₂SeSO₃ solution is rapidly injected into the CdCl₂ solution containing mercaptoacetic acid while heating. Heating is continued for 1 hour. After the reaction is complete, a CdSe QDs solution is obtained. (2) Preparation of PDDA-modified graphene; A graphene oxide solution and a PDDA solution were mixed, hydrazine hydrate was added, and the mixture was heated to react. The reaction solution was then repeatedly washed and centrifuged to obtain a black solid. PDDA-modified graphene was prepared by freeze-drying a black solid under vacuum. Preferably, the graphene oxide solution and 20% PDDA solution are placed in a 250 mL flask and stirred uniformly at room temperature for 30 min. Then, 0.5 mL of 80% hydrazine hydrate is added to the flask, and the mixture is stirred under heating conditions for 24 h. The reaction solution is repeatedly washed with deionized water and centrifuged to remove unreacted hydrazine hydrate. Finally, the obtained black solid is freeze-dried under vacuum to obtain dry PDDA-GR solid. Ultrapure water is added and the solid is ultrasonically dispersed to obtain a 0.1 mg / mL PDDA-GR dispersion. (3) Preparation of cadmium selenide quantum dot-graphene composite material; PDDA-modified graphene was dispersed in a cadmium selenide quantum dot solution under ultrasonic conditions, and after a period of reaction, a cadmium selenide quantum dot-graphene composite material was obtained. (4) Preparation of titanium dioxide nanorods grown on FTO conductive glass; Tetrabutyl titanate was added to hydrochloric acid and stirred for a period of time. The solution was then added to a reaction vessel, and FTO conductive glass was placed vertically at the bottom of the reaction vessel with the conductive surface facing the inner wall of the reaction vessel. After thermal reaction, TiO2 nanorod arrays grown on FTO conductive glass were obtained. (5) Preparation of cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanodes; A solution of cadmium selenide quantum dots and graphene composite material was drop-coated onto an FTO electrode on which TiO2 was grown. After natural drying, a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode was obtained.
[0007] In some embodiments, in step (3), equal volumes of cadmium selenide quantum dot solution and PDDA-modified graphene dispersion are taken. Under ultrasonic conditions, cadmium selenide quantum dot solution is slowly added to the PDDA-modified graphene dispersion at a rate of 1-2 drops per second. After mixing, ultrasonication is continued for 30 minutes to obtain cadmium selenide quantum dot and graphene composite material.
[0008] In some embodiments, in step (4), 0.4 ml of tetrabutyl titanate is added to 18% hydrochloric acid and stirred for about 30 minutes. The solution is then added to a 50 ml reactor. The FTO conductive glass is placed vertically at the bottom of the reactor with the conductive surface facing the inner wall of the reactor. The reactor is heated at 150°C for 4 hours. After cooling to room temperature, the glass is removed and washed to obtain a TiO2 nanorod array grown on the FTO conductive glass.
[0009] Secondly, the present invention provides an application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode. Preferably, the cadmium selenide quantum dot and graphene composite material sensitized titanium dioxide nanorod photoanode is used for photoelectric conversion and catalytic oxidation of ascorbic acid.
[0010] In some embodiments, the application includes the following steps: using a 10ml sealed H-type electrolytic cell, with the two chambers separated by a Nafion 117 proton exchange membrane, adding 0-0.12M ascorbic acid to the PBS electrolyte at the photoanode, and using nitrogen to remove excess oxygen.
[0011] In some embodiments, the anode light source is a 300W xenon lamp equipped with an AM1.5G simulated sunlight filter, and the light intensity on the electrode surface is 80-100mW / cm². 2 .
[0012] In some embodiments, the cathode employs a Pt / C catalyst.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: 1. This invention proposes the preparation and application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode. By modifying graphene with PDDA and CdSe QDs with mercaptoacetic acid, they can be linked by electrostatic adsorption, which is reliable and improves the problem of insufficient conductivity of quantum dots. A rod-shaped TiO2 photoanode with a large surface area and excellent electron transport efficiency is synthesized by high temperature and high pressure in a reactor.
[0014] 2. The cadmium selenide quantum dot-graphene composite material (CdSe QDs-PGR) prepared in this invention has a good response to visible light and, as a sensitizer, greatly broadens the spectral absorption range of the TiO2 photoanode; the prepared cadmium selenide quantum dot / graphene sensitized titanium dioxide nanorod (CdSe QDs-PGR / TiO2 NRAs / FTO) photoanode can effectively generate photocurrent in neutral PBS electrolyte containing ascorbic acid, catalyzing the oxidation of ascorbic acid.
[0015] 3. The cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorods (CdSe QDs-PGR / TiO2 NRAs / FTO) photoanode prepared by the method of this invention has a simple synthesis method and low cost. This material exhibits excellent photoelectric conversion ability. It has been verified that this material can broaden the spectral absorption range of TiO2 to 546 nm, and the assembled battery can achieve 187.65 μW / cm² under visible light. 2 Its energy output and open-circuit potential of 0.75V. Attached Figure Description
[0016] Figure 1 This is a SEM image of the front side of TiO2 nanorods prepared by a photoanode preparation method for cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorods provided in Example 1 of this invention. Figure 2 a is Figure 1 SEM image of the cross-section of TiO2 nanorods. Figure 2 b is Figure 1 SEM image of the side of a TiO2 nanorod; Figure 3 This is a TEM image of cadmium selenide quantum dots prepared by a photoanode preparation method for cadmium selenide quantum dots / graphene-sensitized titanium dioxide nanorods provided in Example 1 of this invention. Figure 4 This is an XRD pattern of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode (CdSe QDs-PGR / TiO2NRAs / FTO) and a TiO2 NRAs / FTO prepared by a method for preparing cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanodes provided in Example 1 of this invention. Figure 5 a is the ultraviolet-visible (UV-Vis) absorption spectrum of cadmium selenide quantum dots (CdSe QDs) prepared by a photoanode preparation method of cadmium selenide quantum dots / graphene-sensitized titanium dioxide nanorods provided in Example 1 of this invention; wherein, the horizontal axis is wavelength and the vertical axis is absorbance. Figure 5 b is the absorption spectrum corresponding to the cadmium selenide quantum dots in Example 2 of the present invention; Figure 5 c is the absorption spectrum corresponding to the cadmium selenide quantum dots in Example 3 of the present invention; Figure 6 Image a is the luminescence of cadmium selenide quantum dots and cadmium selenide quantum dot and graphene composite material prepared by the photoanode preparation method of cadmium selenide quantum dot / graphene sensitized titanium dioxide nanorods provided in Example 1 of this invention under ultraviolet light. Figure 6 b corresponds to Example 2; Figure 6 c corresponds to Example 3; Figure 7 This is the power density of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode prepared by a method for preparing cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanodes according to Example 1 of the present invention at different voltages. Figure 8 This refers to the power density of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode prepared by a method provided in Example 1 of this invention, under different ascorbic acid concentrations. Detailed Implementation
[0017] The present invention will be further described below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and should not be used to limit the scope of protection of the present invention.
[0018] Unless otherwise specified, the experimental methods used in the following examples are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0019] This invention provides a method for preparing a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode, characterized by comprising the following steps: (1) Preparation of cadmium selenide quantum dot solution; A certain amount of selenium powder was dispersed in anhydrous sodium sulfite solution to prepare Na2SeSO3 solution; mercaptoacetic acid was dispersed in CdCl2 solution and adjusted to alkalinity, then Na2SeSO3 solution was added and the reaction was heated to prepare cadmium selenide quantum dot solution. (2) Preparation of PDDA-modified graphene; A graphene oxide solution and a PDDA solution were mixed, hydrazine hydrate was added, and an addition reaction was carried out. The reaction solution was then repeatedly washed and centrifuged to obtain a black solid. PDDA-modified graphene was prepared by freeze-drying a black solid under vacuum. (3) Preparation of cadmium selenide quantum dot-graphene composite material; PDDA-modified graphene was dispersed in a cadmium selenide quantum dot solution under ultrasonic conditions, and after a period of reaction, a cadmium selenide quantum dot-graphene composite material was obtained. (4) Preparation of titanium dioxide nanorods grown on FTO conductive glass; Tetrabutyl titanate was added to hydrochloric acid and stirred for a period of time. The solution was then added to a reaction vessel, and FTO conductive glass was placed vertically at the bottom of the reaction vessel with the conductive surface facing the inner wall of the reaction vessel. After thermal reaction, TiO2 nanorod arrays grown on FTO conductive glass were obtained. (5) Cadmium selenide quantum dot and graphene composite material sensitized titanium dioxide nanorod photoanode; A solution of cadmium selenide quantum dots and graphene composite material was drop-coated onto an FTO electrode on which TiO2 was grown. After natural drying, a cadmium selenide quantum dot and graphene composite material sensitized titanium dioxide nanorod photoanode was obtained.
[0020] It should be noted that in step (1), the amount of anhydrous sodium sulfite used is 1.58g, the amount of CdCl2 solution used is 20ml with a concentration of 5mM, the amount of mercaptoacetic acid used is 20μl, and the amount of Na2SeSO3 solution used is 0.5ml.
[0021] In some embodiments, in step (1), at a temperature of 40-100°C, Na2SeSO3 solution is rapidly injected into a mercaptoacetic acid solution dispersed in CdCl2 solution, and the mixture is heated for 1-2 hours.
[0022] This invention also provides an application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode, wherein the cadmium selenide quantum dot and graphene composite material sensitized titanium dioxide nanorod photoanode is used for photoelectric conversion and catalytic oxidation of ascorbic acid.
[0023] The present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited thereto.
[0024] Example 1 A method for preparing a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode includes the following steps: (1) Preparation of cadmium selenide quantum dot solution; a. First, mix 0.39g of selenium powder with 1.58g of anhydrous sodium sulfite, add 20ml of water as a solvent, heat at 90℃ while stirring continuously, and after the reaction is complete, add ultrapure water to make up to 50ml to obtain Na2SeSO3 solution. b. Add 20 μl of mercaptoacetic acid to 20 ml of 5 mM CdCl2 solution, then adjust the pH to 10 with 0.5 M NaOH, and add ultrapure water to make up to 50 ml. Rapidly inject 0.5 ml of Na2SeSO3 solution into the CdCl2 solution containing mercaptoacetic acid at 100 °C, and continue heating for 1 hour. After the reaction is complete, a cadmium selenide quantum dot (CdSe QDs) solution is obtained. (2) Preparation of PDDA-modified graphene; a. Place 100 ml of graphene oxide solution with a concentration of 5 mg / ml and 20% PDDA solution in a 250 mL flask, stir evenly at room temperature for 30 min, then add 0.5 mL of 80% hydrazine hydrate to the flask, and stir under heating conditions for 24 h; b. The reaction solution was repeatedly washed and centrifuged with deionized water to remove unreacted hydrazine hydrate. Finally, the black solid obtained was freeze-dried under vacuum to obtain dry PDDA-GR solid. Ultrapure water was added and ultrasonically dispersed to obtain a 0.1 mg / ml PDDA-GR dispersion. (3) Preparation of cadmium selenide quantum dot-graphene composite material (CdSe QDs-PGR); Take equal volumes of CdSe QDs solution and PDDA-GR dispersion. While the PDDA-GR dispersion is sonicated, slowly add CdSe QDs solution dropwise, controlling the amount at 1-2 drops per second. After mixing, continue sonicating for 30 minutes to obtain the cadmium selenide quantum dot-graphene composite material (CdSe QDs-PGR).
[0025] (4) Preparation of titanium dioxide nanorods grown on FTO conductive glass; Add 0.4 ml of tetrabutyl titanate to 10 ml of 18% hydrochloric acid and stir for about 30 minutes. Add the solution to a 50 ml reactor. Place an FTO conductive glass column vertically at the bottom of the reactor with the conductive side facing the inner wall. Heat at 150°C for 4 hours. After cooling to room temperature, remove and wash to obtain a TiO2 nanorod array grown on the FTO conductive glass.
[0026] (5) Preparation of cadmium selenide quantum dot and graphene composite material sensitized titanium dioxide nanorod photoanode; Preparation of cadmium selenide quantum dot graphene composite material supported on titanium dioxide nanorods grown on FTO conductive glass (CdSe QDs-PGR / TiO2 NRAs / FTO) photoanode Take 100 μL of CdSe QDs-PGR solution and drop it directly onto the FTO electrode on which TiO2 has been grown. Let it air dry to obtain the CdSe QDs-PGR / TiO2 NRAs / FTO photoanode.
[0027] In this embodiment, after synthesis, the surface, cross-section, and side surfaces of the TiO2 NRAs synthesized in step (4) were characterized by SEM, such as... Figure 1 , Figure 2 a, Figure 2 As shown in b, TiO2 has a bottom-up vertical growth structure with a height of about 1-2 μm and its growth is very dense.
[0028] The CdSe QDs solution from step (1)b of Example 1 was laid on an ultrathin copper grid and subjected to transmission electron microscopy (TEM) testing. The TEM image is shown below. Figure 3 As shown, CdSe QDs have a diameter of 6-8 nm, and lattice fringes of 0.22 nm were also observed.
[0029] The XRD patterns of TiO2 NRAs / FTO and CdSe QDs-PGR / TiO2 NRAs / FTO in steps (4) and (5) of Example 1 are as follows: Figure 4 As shown, in the CdSe QDs-PGR / TiO2 NRAs / FTO, besides the characteristic peaks of TiO2 NRAs, the characteristic peaks around 24°, 25°, and 42° represent the crystal plane diffraction of the (100), (002), and (101) crystal planes of the zincblende crystal form, respectively. (The last sentence appears to be incomplete and possibly refers to a different context.) Figure 3 The 0.22 nm lattice fringes also indicate that CdSe quantum dots were successfully deposited on the TiO2 NRAs surface.
[0030] The CdSe QDs-PGR prepared in the examples was subjected to ultraviolet-visible absorption spectroscopy testing, such as... Figure 5 As shown in a, CdSe QDs-PGR can absorb visible light up to 546 nm.
[0031] The CdSe QDs-PGR and CdSe QDs prepared in the examples were irradiated with ultraviolet light, such as... Figure 6 As shown in Figure a, CdSeQDs can emit red light, while the luminescence intensity of CdSeQDs-PGR is significantly lower.
[0032] The application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode in a photocatalytic fuel cell includes the following steps: The CdSe QDs-PGR / TiO2 NRAs / FTO prepared in Example 1 was placed in a 10ml sealed H-type electrolytic cell, with a Nafion 117 proton exchange membrane separating the two chambers. Ascorbic acid (0-0.12M) was added to the PBS electrolyte at the photoanode, and excess oxygen was removed using nitrogen. A Pt / C catalyst was used at the cathode, loaded onto a 3mm glassy carbon electrode, and oxygen was continuously bubbled into the PBS electrolyte at the cathode. The anode light source was a 300W xenon lamp equipped with an AM1.5G simulated sunlight filter, and the light intensity at the electrode surface was set to 100mW / cm². 2 .
[0033] Summary: Results are attached. Figure 7 , Figure 8 As shown, the results indicate that the photoelectrode can effectively generate photocurrent in PBS electrolyte containing ascorbic acid under light source irradiation, catalyzing the oxidation of ascorbic acid. Specifically, within the voltage range of 0-0.8 V, it can generate 187.65 μW / cm² at 0.5 V. 2 It has the highest power density in the range of ascorbic acid concentration of 0-0.12M, and at the concentration of ascorbic acid of 0.1M. Example 2
[0034] The preparation method of a cadmium selenide quantum dot / graphene sensitized titanium dioxide nanorod photoanode is the same as that in Example 1, and will not be repeated here. The difference is that the heating temperature in step (1)b is 70°C, and the other steps are the same as those in Example 1.
[0035] The CdSe QDs-PGR prepared in the examples was subjected to ultraviolet-visible absorption spectroscopy testing, such as... Figure 5 As shown in b, CdSe QDs-PGR can absorb visible light up to 497 nm.
[0036] The CdSe QDs-PGR and CdSe QDs prepared in the examples were irradiated with ultraviolet light, such as... Figure 6 As shown in b, CdSeQDs can emit yellow light, while the luminescence intensity of CdSeQDs-PGR is significantly lower.
[0037] The application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode in a photocatalytic fuel cell is the same as that in Example 1, except that the CdSe QDs-PGR / TiO2 NRAs / FTO photoanode used in Example 2 was prepared. The rest of the steps are the same and will not be repeated. Example 3
[0038] The preparation method of a cadmium selenide quantum dot / graphene sensitized titanium dioxide nanorod photoanode is the same as that in Example 1, and will not be repeated here. The difference is that the heating temperature in step (1)b is 40°C, and the other steps are the same as those in Example 1.
[0039] The CdSe QDs-PGR prepared in the examples was subjected to ultraviolet-visible absorption spectroscopy testing, such as... Figure 5 As shown in c, CdSe QDs-PGR can absorb visible light up to 470 nm.
[0040] The CdSe QDs-PGR and CdSe QDs prepared in the examples were irradiated with ultraviolet light, such as... Figure 6 As shown in c, CdSeQDs can emit blue-green light, while the luminescence intensity of CdSeQDs-PGR is significantly lower.
[0041] The application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode in a photocatalytic fuel cell is the same as that in Example 1, except that the CdSe QDs-PGR / TiO2 NRAs / FTO photoanode used in Example 2 was prepared. The rest of the steps are the same and will not be repeated.
[0042] This invention discloses the preparation and application of a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode, belonging to the field of photoelectrocatalysis technology. Addressing the challenges of achieving high-power output and the high cost of photoelectrodes in existing photocatalysis methods, this invention synthesizes a CdSe QDs-PGR composite material by modifying CdSe quantum dots with mercaptoacetic acid and graphene with PDDA, using a simple electrostatic adsorption method. This solves the problem of insufficient conductivity of the quantum dots themselves, reduces photo-recombination phenomena, and effectively broadens the spectral absorption range as a sensitizer for the photoelectrode. Furthermore, the invention utilizes a one-step process under high temperature and pressure in a reactor to prepare TiO2 NRAs grown on FTO conductive glass. This method is simple, inexpensive, and the rod-shaped TiO2 exhibits a higher surface area and more efficient electron transfer.
[0043] The CdSe QDs-PGR / TiO2 NRAs / FTO photoelectrode prepared by this invention can effectively perform photoelectric conversion in photocatalytic fuel cells, generating photocurrent while catalytically oxidizing ascorbic acid, thus greatly improving power output. Experiments have confirmed that the optimal process parameters are: CdCl2 solution pH 10, reaction temperature 100℃, hydrochloric acid 10 ml, and tetrabutyl titanate 0.4 ml (Example 1). This technology uses inexpensive and readily available raw materials, and the process is simple and controllable, providing a new approach for the development of clean energy materials.
[0044] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode, characterized in that, Includes the following steps: (1) Preparation of cadmium selenide quantum dot solution; A certain amount of selenium powder was dispersed in anhydrous sodium sulfite solution to prepare Na2SeSO3 solution; mercaptoacetic acid was dispersed in CdCl2 solution and adjusted to alkalinity; at a certain temperature, Na2SeSO3 solution was rapidly injected into CdCl2 solution containing mercaptoacetic acid; after reacting for a period of time, cadmium selenide quantum dot solution was prepared. (2) Preparation of PDDA-modified graphene; A black solid was obtained by mixing a graphene oxide solution and a PDDA solution, adding hydrazine hydrate, and heating the mixture. The reaction solution was then repeatedly washed and centrifuged. PDDA-modified graphene was prepared by freeze-drying a black solid under vacuum. (3) Preparation of cadmium selenide quantum dot-graphene composite material; Take equal volumes of cadmium selenide quantum dot solution and PDDA-modified graphene dispersion. While the PDDA-modified graphene dispersion is under ultrasonic conditions, slowly add cadmium selenide quantum dot solution to it, controlling the amount to 1-2 drops per second. After mixing, continue ultrasonication for 30 minutes to obtain cadmium selenide quantum dot and graphene composite material. (4) Preparation of titanium dioxide nanorods grown on FTO conductive glass; Tetrabutyl titanate was added to hydrochloric acid and stirred for a period of time. The solution was then added to a reaction vessel, and FTO conductive glass was placed vertically at the bottom of the reaction vessel with the conductive surface facing the inner wall of the reaction vessel. After thermal reaction, TiO2 nanorod arrays grown on FTO conductive glass were obtained. (5) Preparation of cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanodes; A solution of cadmium selenide quantum dots and graphene composite material was drop-coated onto an FTO electrode on which TiO2 was grown. After natural drying, a cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode was obtained.
2. The method for preparing the cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode according to claim 1, characterized in that, In step (1), the amount of anhydrous sodium sulfite used is 1.58 g, the amount of CdCl2 solution used is 20 ml with a concentration of 5 mM, the amount of mercaptoacetic acid used is 20 μl, and the amount of Na2SeSO3 solution used is 0.5 ml.
3. The method for preparing the cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode according to claim 2, characterized in that, In step (1), at a temperature of 40-100℃, the Na2SeSO3 solution is rapidly injected into the CdCl2 solution containing mercaptoacetic acid and heated continuously for 1-2 hours.
4. The method for preparing the cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode according to claim 1, characterized in that, In step (4), 0.4 ml of tetrabutyl titanate was added to 18% hydrochloric acid and stirred for 30 minutes. The solution was then added to a 50 ml reactor. The FTO conductive glass was placed vertically at the bottom of the reactor with the conductive side facing the inner wall of the reactor. The reactor was heated at 150°C for 4 hours. After cooling to room temperature, the reactor was removed and washed to obtain a TiO2 nanorod array grown on the FTO conductive glass.
5. The application of the cadmium selenide quantum dot / graphene-sensitized titanium dioxide nanorod photoanode obtained by the preparation method according to claim 1, characterized in that, The cadmium selenide quantum dot and graphene composite material sensitized titanium dioxide nanorod photoanode is used for photoelectric conversion and catalytic oxidation of ascorbic acid.
6. The application according to claim 5, characterized in that, Includes the following steps: A 10 ml sealed H-type electrolytic cell was used, with the two chambers separated by a Nafion 117 proton exchange membrane. 0-0.12 M ascorbic acid was added to the PBS electrolyte at the photoanode, and excess oxygen was removed using nitrogen gas.
7. The application according to claim 6, characterized in that, The anode light source is a 300 W xenon lamp equipped with an AM 1.5 G simulated sunlight filter, and the light intensity on the electrode surface is 80-100 mW / cm². 2 .
8. The application according to claim 7, characterized in that, The cathode uses a Pt / C catalyst.
Citation Information
Patent Citations
Cadmium selenide quantum dot sensitized titanium dioxide nano-rod optical electrode, and preparation and application thereof
CN106637289A